Milk composition in Huacaya alpaca (Vicugna pacos) and llama (Lama glama) - Ormachea Valdez, Edwin (2021)
The aim of this study was to determine the physicochemical characteristics of milk in alpacas and llamas, considering two agroecological zones in the case of the alpaca. 40 Huacaya alpacas and 20 female llamas that were between 40 and 45 days of lactation were used. The animal husbandry system was extensive. The composition of total solids (%), gross energy (MJ/100 g), ash (%), fat (%), non-fatty solids (%), density (g/cm3), protein (%), lactose were determined. (%), salts (%), pH, freezing point (ºC) and somatic cell count (cells/ml x 1000). It is concluded that the physicochemical composition of milk is similar between llamas and alpacas and that the agroecological zone influences the composition of milk in Huacaya alpacas.